Interrogating existentialism in simone de beauvoir’s le sang des autres (2020)
This paper attempts to present an existential analysis of Simone de Beauvoir’s Le sang des autres. The study explores Le sang des autres’ unique portrayal of outstanding features of French Existentialism namely, freedom and choice. It exposes characters’ exercise of existential freedom in their political choices as well as in their sexual relationships. Using Existentialism as a theoretical framework, the study presents Simone de Beauvoir’s literary characters as they make choices freely and thereafter assume full responsibility for their actions. Through the use of examples found within the text, the study further demonstrates that choice is consequential and could result in the suffering of the “Others.” From the analysis, it is obvious that Simone de Beauvoir, projects authentic existence, as can be seen in Jean Blomart the protagonist and Hélène, one of his lovers. Authentic existence emphasizes that individuals must readily own up and accept full responsibility for their actions, whether such consequences are positive or negative.